Phenotype, Susceptibility, Autoimmunity, and Immunotherapy Between Kawasaki Disease and Coronavirus Disease-19 Associated Multisystem Inflammatory Syndrome in Children - Chen, Ming-Ren; Kuo, Ho-Chang; Lee, Yann-Jinn; Chi, Hsin; Li, Sung Chou; Lee, Hung-Chang; Yang, Kuender D. (Frontiers in Immunology, 2021)
Covid-19 in children is usually mild but some are susceptible to a Kawasaki disease (KD)-like multisystem inflammatory syndrome in children (MIS-C) in convalescent stage, posing a need to differentiate the phenotype, susceptibility, autoimmunity and immunotherapy between KD and MIS-C, particularly in the upcoming mass vaccination of Covid-19. MIS-C is prone to gastrointestinal symptoms, coagulopathy and shock in addition to atypical KD syndrome with fever, mucocutaneous lesions, lymphadenopathy and/or cardiovascular events. MIS-C manifests KD-like symptoms which alert physicians to early recognize and adopt the KD treatment regimen for patients with MIS-C. Vice versa, MIS-C linked to Covid-19 teaches us infection-associated autoimmune vasculitis. Studies on genetic susceptibility have identified certain HLA locus and toll-like receptor (TLR) associated with KD and/or Covid-19. Certain HLA subtypes such as HLA-DRB1 and HLA-MICA A4 are associated with KD, HLA- B*46:01 is proposed to be the risk allele of severe Covid-19 infection, and blood group O type is a protective factor of Covid-19. The autoimmune vasculitis of KD, KD shock syndrome (KDSS) or MIS-C is mediated by a genetic variant of HLA, FcR and/or ADE resulting in hyperinflammation with Th17/Treg imbalance with augmented T helper 17 (Th17)/Th1 mediators: IL6, IL10, IP-10, IFN and IL17A, and lower expression of Treg-signaling molecules, FoxP3 and TGF. There are certain similarity and difference of phenotypes, susceptibility and pathogenesis among KD, KDSS and MIS-C, by which a physician can make early protection, prevention and precision treatment of the diseases. Evolution of immunotherapies for the diseases has shown that IVIG alone or combined with corticosteroids is the standard treatment for KD, KDSS and MIS-C. However, certain portion of patients who revealed a treatment resistance to IVIG or IVIG plus corticosteroids, posing a need to early identify the immunopathogenesis, to protect hosts with genetic susceptibility, and to combat Th17/Treg imbalance by anti-cytokine or pro-Treg for reversal of the hyperinflammation and IVIG resistance. Based on physiological and pathological immunity of the diseases under genetic susceptibility and host milieu conditions, a series of sequential regimens are provided to develop a so-called “Know thyself, enemy (pathogen) and ever-victorious” strategy for prevention and immunotherapy of KD and/or MISC.